2021
DOI: 10.3390/cancers13143594
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory and Immune-Nutritional Prognostic Markers in Patients Undergoing Surgical Resection for Biliary Tract Cancers

Abstract: The relationship between immune-nutritional status and tumor growth; biological aggressiveness and survival, is still debated. Therefore, this study aimed to evaluate the prognostic performance of different inflammatory and immune-nutritional markers in patients who underwent surgery for biliary tract cancer (BTC). The prognostic role of the following inflammatory and immune-nutritional markers were investigated: Glasgow Prognostic Score (GPS), modified Glasgow Prognostic Score (mGPS), Prognostic Index (PI), N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Lin et al compared the prognostic value of GPS, mGPS, PI, NLR, PLR, LMR, and PNI in 200 patients with ICC, and although this study showed that all these scores had significant prognostic value, LMR was found to be the best prognostic factor in a multifactorial analysis (20). Similar conclusions were reached by Simone Conci et al in patients with biliary tract tumors (21).The prognostic value of LMR had also been demonstrated in other malignancies, such as hepatocellular carcinoma, lung cancer, colorectal cancer, etc. (22)(23)(24).This study also discovered that patients in the high NLR group or low LMR group had a worse survival prognosis.…”
Section: Discussionmentioning
confidence: 51%
“…Lin et al compared the prognostic value of GPS, mGPS, PI, NLR, PLR, LMR, and PNI in 200 patients with ICC, and although this study showed that all these scores had significant prognostic value, LMR was found to be the best prognostic factor in a multifactorial analysis (20). Similar conclusions were reached by Simone Conci et al in patients with biliary tract tumors (21).The prognostic value of LMR had also been demonstrated in other malignancies, such as hepatocellular carcinoma, lung cancer, colorectal cancer, etc. (22)(23)(24).This study also discovered that patients in the high NLR group or low LMR group had a worse survival prognosis.…”
Section: Discussionmentioning
confidence: 51%
“…Inflammatory markers have recently emerged as potential prognostic factors for several malignancies including biliary tract cancers. 20 The possible relationship between inflammatory markers and oncologic outcomes arises from the role of chronic inflammation in developing cancers. According to some previous studies, systemic inflammation could be either cause or effect of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the ability to escape immune destruction is now considered within the fourteen core hallmarks of cancer [16]. Many studies investigated the relationship between altered immune pro le at diagnosis and survival in CRC [17,18,[27][28][29] and other solid tumours [12,15,30,31], but none assessed longitudinal changes in these parameters nor the association of Pre-CBC and post-operative survival. In fact, this is the rst study ever that investigated the relationship between pre-diagnosis immune pro le (at least 24 months before surgery) and cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that cancer progression may result from imbalances between tumor growth and the host immune surveillance [10,11]. Interestingly, several studies have found a relevant association between survival of patients with different cancers and alterations in peripheral immune cells count [12][13][14][15]. The latter may in fact play a role as circulating biomarkers of an immune shift leading to tumor escape [16].…”
Section: Introductionmentioning
confidence: 99%